Identifying Barriers in the Home Environment among Urban Community-Dwelling Older Adults with Functional Difficulty: A Multi-Method Pilot Study. Issue 4 (2nd October 2019) - Russell, David; Oberlink, Mia R.; Onorato, Nicole; Feinberg, Jodi L.; Bowles, Kathryn H.; Szanton, Sarah L.
ABSTRACT: Homes in dense urban areas can present unique challenges to community-dwelling older adults. This multi-method pilot study explored home environment barriers among lower-income urban community-dwelling older adults with functional difficulty using the In-Home Occupational Performance Evaluation ( N = 15). Additional data were collected from interviews with community service providers ( N = 7). Home environment barriers, including clutter and stairs, limited the ability of many community dwelling adults to perform routine tasks. Service providers felt that home assessments were helpful for identifying problematic activities and barriers early on before they became larger problems, especially for older adults with limited social supports and mental health problems. Our findings support interdisciplinary interventions to reduce barriers in the home environments of older adults.